2019
DOI: 10.3390/en12203963
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Heat Transfer Mechanism of Air-Blast-Spray-Cooling System with a Two-Phase Ejector Loop for Aeronautical Application

Abstract: This paper presents an air-oriented spray cooling system (SCS) integrated with a two-phase ejector for the thermal management system. Considering its aeronautical application, the spray nozzle in the SCS is an air-blast one. Heat transfer performance (HTP) of air-water spray cooling was studied experimentally on the basis of the ground-based test. Factors including pressure difference between water-inlet-pressure (WIP) and spray cavity one (PDWIC) and the spray volumetric flow rate (SVFR) were investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The ability to dissipate heat generated by electronic circuits is required in high-power electronic applications. Liquid coolants are an efficient method of extracting high heat power from a heated surface (Li et al, 2019). It is necessary to have a low surface superheat and a low mass flow rate to build a compact cooling system for high-powered technological devices.…”
Section: Literature Review and Objectivementioning
confidence: 99%
“…The ability to dissipate heat generated by electronic circuits is required in high-power electronic applications. Liquid coolants are an efficient method of extracting high heat power from a heated surface (Li et al, 2019). It is necessary to have a low surface superheat and a low mass flow rate to build a compact cooling system for high-powered technological devices.…”
Section: Literature Review and Objectivementioning
confidence: 99%
“…In general, a better spray cooling performance can be acquired by decreasing the Sauter Mean Diameter (SMD) of the spray droplet size [10] and increasing the velocity of droplet-impacting [11]. It has been found that the twin-fluid atomization method can obtain a higher quality of spray, and the air-blast nozzle is one representative example [12][13][14]. On the other side, the cooling ability of the spray shows that the heat transfer characteristics are influenced significantly by low gravity, which may result in a lower cooling effectiveness than higher gravity and normal gravity due to the increasing thickness of the average liquid film [15].…”
Section: Introductionmentioning
confidence: 99%